2014
DOI: 10.7314/apjcp.2014.15.22.9699
|View full text |Cite
|
Sign up to set email alerts
|

The XPD Lys751Gln Polymorphism has Predictive Value in Colorectal Cancer Patients Receiving Oxaliplatin-Based Chemotherapy: a Systemic Review and Meta-analysis

Abstract: Background: The predictive value of the xeroderma pigmentosum group D (XPD) Lys751Gln polymorphism regarding clinical outcomes of patients with colorectal cancer (CRC) receiving oxaliplatin-based chemotherapy has been evaluated in numerous published studies, but the results remain inconclusive. Therefore, we performed a meta-analysis to determine the precise role of the XPD Lys751Gln polymorphism in this clinical situation and optimize individual chemotherapy. Materials and Methods: A multiple search strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our findings for ERCC1 rs11615 and XPD rs13181 are supported in four meta-analyses (Yin et al, 2011;Qian et al, 2014;Ma et al, 2015;Shahnam et al, 2016). The other biomarkers have not been studied as extensively.…”
Section: Discussionsupporting
confidence: 69%
“…Our findings for ERCC1 rs11615 and XPD rs13181 are supported in four meta-analyses (Yin et al, 2011;Qian et al, 2014;Ma et al, 2015;Shahnam et al, 2016). The other biomarkers have not been studied as extensively.…”
Section: Discussionsupporting
confidence: 69%
“…Previous research has shown that the wild-type genotype AA is associated with a higher DNA repair capacity as compared to that of the CC genotype in the rs13181 polymorphism [26]. Qian et al suggested that the ERCC2 rs13181 A>C polymorphism has prognostic value in patients with colorectal cancer undergoing oxaliplatin-based chemotherapy [27]. A meta-analysis demonstrated that the rs13181 A>C and rs1799793 G>A polymorphisms are significantly correlated with the response to chemotherapy for patients with osteosarcoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Xeroderma pigmentosum group D (XPD) gene facilitates DNA repair by denaturing damaged site. Previous findings showed the close relationship between SNP of XPD gene at 751 st locus ISSN 0970-938X www.biomedres.info and the sensitivity to platinum based drugs [15][16][17]. Moreover, study has found that Glutathione S-Transferase P1 (GSTP1) activity can be down-regulated by SNP of GSTP1 gene at 105 th locus, thus weakening platinum drug sensitivity [18,19].…”
Section: Introductionmentioning
confidence: 93%